2018
DOI: 10.6061/clinics/2018/e261
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the efficiency of 22G versus 25G needles in EUS-FNA for solid pancreatic mass assessment: A systematic review and meta-analysis

Abstract: Our aim in this study was to compare the efficiency of 25G versus 22G needles in diagnosing solid pancreatic lesions by EUS-FNA. We performed a systematic review and meta-analysis. Studies were identified in five databases using an extensive search strategy. Only randomized trials comparing 22G and 25G needles were included. The results were analyzed by fixed and random effects. A total of 504 studies were found in the search, among which 4 randomized studies were selected for inclusion in the analysis. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 33 publications
0
37
1
1
Order By: Relevance
“…Furthermore, a meta-analysis of randomized controlled trials did not show a significant difference between different needle sizes. 32 In summary, this is the largest multicenter study to specifically compare the effectiveness and safety of EUS-FNA versus EUS-FNB for LN sampling. Both EUS-FNA and EUS-FNB are safe for the diagnosis of LNs.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a meta-analysis of randomized controlled trials did not show a significant difference between different needle sizes. 32 In summary, this is the largest multicenter study to specifically compare the effectiveness and safety of EUS-FNA versus EUS-FNB for LN sampling. Both EUS-FNA and EUS-FNB are safe for the diagnosis of LNs.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, we included different needles sizes for FNA and FNB groups. However, a meta-analysis including just RCT did not show significant difference between different needles sizes [8]. We did not evaluate the needles regarding the various types of pancreatic masses.…”
Section: Resultsmentioning
confidence: 89%
“…EUS-FNA of solid pancreatic lesions is a safe procedure, associated with high diagnostic accuracy, usually above 85 %, and ▶ Table 3 Comparison between FNA and FNB based on EUS-tissue sampling access. typically better when ROSE is available [6][7][8]. However, the diagnostic accuracy of EUS-FNA with cytology is insufficient to verify cellular arrangement and tissue architecture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of a number of randomized clinical trials, one study showed a tendency towards higher accuracy of the 25-G needle [ 43 ], whereas the others showed a similar diagnostic yield of malignancy [ 44 , 45 , 46 , 47 , 48 , 49 ]. Studies comparing FNA with 22-G and 25-G needles were also reviewed as five meta-analyses [ 41 , 50 , 51 , 52 , 53 ]. However, more recent meta-analyses showed different results.…”
Section: Needle Sizementioning
confidence: 99%